NF-κB as an Inflammatory Biomarker in Thin Endometrium: Predictive Value for Live Birth in Recurrent Implantation Failure - Zercan Kalı; Pervin Karlı; Fatma Tanılır; Pınar Kırıcı; Serhat Ege (Diagnostics)
Background: Recurrent implantation failure (RIF) poses a major challenge in assisted reproductive technologies, with thin endometrium (≤7 mm) being a frequently observed yet poorly understood condition. Emerging evidence implicates nuclear factor-kappa B (NF-κB), a key transcription factor in inflammatory signaling, in impaired endometrial receptivity. However, its clinical relevance and prognostic value for live birth outcomes still need to be fully elucidated. Objective: We aim to evaluate the expression levels of endometrial NF-κB in patients with RIF and thin endometrium and to determine its potential as a predictive biomarker for live birth outcomes following IVF treatment. Methods: In this prospective case–control study, 158 women were categorized into three groups: Group 1 (RIF with thin endometrium, ≤7 mm, n = 52), Group 2 (RIF with normal endometrium, >7 mm, n = 38), and fertile controls (n = 68). NF-κB levels were assessed using ELISA and immunohistochemical histoscore. Pregnancy outcomes were compared across groups. ROC analysis and multivariable logistic regression were performed to assess the predictive value of NF-κB. Results: NF-κB expression was significantly elevated in Group 1 compared to Group 2 and controls (p = 0.0017). ROC analysis identified a cut-off value of 7.8 ng/mg for live birth prediction (AUC = 0.72, sensitivity 74%, specificity 75%). Multivariable analysis confirmed NF-κB is an independent predictor of live birth (p = 0.045). Histological findings revealed increased NF-κB staining in luminal and glandular epithelial cells in the thin endometrium group. Conclusions: Increased endometrial NF-κB expression is associated with thin endometrium and reduced live birth rates in RIF patients. NF-κB may serve not only as a biomarker of pathological inflammation but also as a prognostic tool for treatment stratification in IVF. Based on findings in the literature, the therapeutic targeting of NF-κB may represent a promising strategy to improve implantation outcomes.